Grazing pressure affects offspring sex ratio in a socially monogamous passerine on the Tibet Plateau. (23rd April 2018) - Li, Shaobin; Shi, Ruirui; Li, Wei; Li, Guopan
Abstract : Livestock grazing can affect habitat structure and availability of arthropod prey for grassland birds, and ultimately determines habitat quality. The habitat quality may affect breeding strategies (e.g. sex ratio adjustment) in bird species, but studies investigating grazing intensity on offspring sex ratio are still rare. In this paper, we examined the effect of grazing intensity by livestock on the secondary sex ratio of an alpine‐steppe passerine, the isabelline wheatear Oenanthe isabellina, on the Tibet Plateau. Offspring sex ratio of isabelline wheatears significantly correlated with a quadratic term – (grazing intensity) 2 . The wheatears nesting in areas grazed at low intensity by mixed livestocks produced significantly more sons than those in ungrazed area (0.41 vs 0.58, Z = –2.836, p = 0.005), while brood sex ratios from other treatments (ungrazing vs intensive grazing and low‐intensity grazing vs intensive grazing) did not differ significantly. Variation in offspring sex ratio was not related to other factors such as maternal condition, paternal condition and other two‐way interactions. These results suggest that breeding birds of grasslands are sensitive to variation in habitat conditions, and provide additional evidence that grazing intensity affects avian reproduction in cryptic ways that are rarely studied. Our findings suggest that flexible management including timely rotational grazing is needed to optimize bird species reproduction and maintain ecosystem health.